Psalmus Hungaricus (Budapest)
3 cilt (1. c. 385 s. ; 2. c. s. [386]-941 ; 3. c. s. [943]-1739)
Keywords: “Psalmus Hungaricus is a three-volume synthesis of Hungarian cultural history presented by the Research Centre for the Humantities of the Loránd Eötvös Research Network in Budapest. It is the most comprehensive overview of the Hungarian past ever published in English. Authors and editors include the most prominent experts of their fields. The work embraces the entire history of the Hungarian nation and state from the earliest beginnings to the end of the twentieth century targeting both scholars and the general public. Cultural history is interpreted in the broadest possible meaning of the concept encompassing the artistic, economic, literary, political, social political milieu of Hungarian civilization. Accordingly, the nine chronological chapters cover political, social, and economic history, history of the language, arts and literature, folk beliefs, religions and churches, physical and political geography, science, technology, manners, everyday life of their respective time periods.“ --